2019
DOI: 10.1111/jcmm.14885
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of WKYMVm peptide on inflammatory osteolysis through regulating NF‐κB and CD9/gp130/STAT3 signalling pathway

Abstract: The balance between bone formation and bone resorption is closely related to bone homeostasis. Osteoclasts, originating from the monocyte/macrophage lineage, are the only cell type possessing bone resorption ability. Osteoclast overactivity is thought to be the major reason underlying osteoclast‐related osteolytic problems, such as Paget's disease, aseptic loosening of prostheses and inflammatory osteolysis; therefore, disruption of osteoclastogenesis is considered a crucial treatment option for these issues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
(131 reference statements)
1
29
0
Order By: Relevance
“…According to our previous study, WKYMVm peptide could activate the FPR2 pathway in MSCs [20]. In this study, we found that when the FPR2 pathway was activated, the expression of ISG15 in mBMSCs was decreased signi cantly compared with the control group without WKYMVm peptide (Figure 2A,2B).…”
Section: Wkymvm Peptide Activated the Fpr2 Pathway Of Mbmscs Resultesupporting
confidence: 58%
See 2 more Smart Citations
“…According to our previous study, WKYMVm peptide could activate the FPR2 pathway in MSCs [20]. In this study, we found that when the FPR2 pathway was activated, the expression of ISG15 in mBMSCs was decreased signi cantly compared with the control group without WKYMVm peptide (Figure 2A,2B).…”
Section: Wkymvm Peptide Activated the Fpr2 Pathway Of Mbmscs Resultesupporting
confidence: 58%
“…Furthermore, exosomes containing many biological molecules, such as proteins, enzymes and miRNAs, which have important physiological or pathological effects [24]. On the other hand, according to our previous studies, WKYMVm peptide, as a powerful activator of FPR2 pathway, can activate the FPR2 pathway in MSCs [20]. However, when the FPR2 pathway of MSCs is activated, what kind of changes will take place, and what impact on the secreted exosomes of MSCs, and what effects of secreted exosomes on the differentiation of macrophages are rarely reported.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To address the question of how FPR2 plays a role in women with CAM, we detected the location and expression of its downstream target proteins. It was reported that FPR2 was closely associated with inflammation and pregnancy immunity adaptation through NF‐κB pathway 20,21 . Accordingly, we hypothesized that FPR2 participated in the process of CAM through PPARγ/NF‐κB pathway.…”
Section: Resultsmentioning
confidence: 90%
“…Our data moreover, indicate an important role for Fpr2/3 in restraining NFκB signalling via inhibition of IκBα degradation, extending our understanding of the receptor’s intracellular signalling pathways (Cooray et al, 2013), as well as highlighting its potential to modulate pro-inflammatory signalling. The modulation of LPS-induced NFκB by Fpr2/3 stimulation has been reported recently in both monocyte (de Gaetano et al, 2019) and osteoclast (Hu et al, 2020) cell lines, suggesting it may be a common feature of macrophage-lineage cells. As microglia are known to rapidly upregulate Fpr2/3 expression following inflammatory insult (Kirkley et al, 2017), this serves as a further indication for the importance of this receptor in inflammatory regulation, emphasising the concept that inflammatory resolution is an intrinsic, programmed part of the inflammatory response (Serhan and Savill, 2005).…”
Section: Discussionmentioning
confidence: 77%